A Comparative Study of Microleakage on Dental Surfaces Bonded with Three Self-Etch Adhesive Systems Treated with the Er:YAG Laser and Bur - Sanhadji El Haddar, Youssef (Biomed Res Int, 2016)
Aim. This study sought to compare the microleakage of three adhesive systems in the context of Erbium-YAG laser and diamond bur cavity procedures. Cavities were restored with composite resin. Materials and Methods. Standardized Class V cavities were performed in 72 extracted human teeth by means of diamond burs or Er-YAG laser. The samples were randomly divided into six groups of 12, testing three adhesive systems (Clearfil s(3) Bond Plus, Xeno® Select, and Futurabond U) for each method used. Cavities were restored with composite resin before thermocycling (methylene blue 2%, 24 h). The slices were prepared using a microtome. Optical microscope photography was employed to measure the penetration. Results. No statistically significant differences in microleakage were found in the use of bur or laser, nor between adhesive systems. Only statistically significant values were observed comparing enamel with cervical walls (p < 0.001). Conclusion. It can be concluded that the Er:YAG laser is as efficient as diamond bur concerning microleakage values in adhesive restoration procedures, thus constituting an alternative tool for tooth preparation.